1999
DOI: 10.1021/jp984730t
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoconvection Phenomena:  A Mechanism for Influence of Magnetic Fields on Electrochemical Processes

Abstract: The objective of this study is to suggest an interaction mechanism for the influence of static magnetic fields on electrochemical processes occurring at a ferromagnetic electrode immersed in a paramagnetic electrolytic solution. The hypothesis is that the magnetic field will cause a transport of all ions due to the difference in the magnetic susceptibility in the solution at the electrode surface. The ion transport induced by the magnetic field is directed from electrode into solution. Experimentally, the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 26 publications
(62 reference statements)
1
79
1
1
Order By: Relevance
“…The shift is anodic for all three metals (Fe, Co, Ni), in contrast to the report of Waskaas and Kharkats [7].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The shift is anodic for all three metals (Fe, Co, Ni), in contrast to the report of Waskaas and Kharkats [7].…”
Section: Discussioncontrasting
confidence: 99%
“…potential of an iron electrode immersed in various paramagnetic iron salt solutions [7]. Even more surprisingly, they found that whereas the shift was in the anodic direction for iron, the potential shifted cathodically for both cobalt and nickel.…”
mentioning
confidence: 97%
“…Unlike NO 3 − , oxygen is uncharged and therefore unaffected by Lorentz force, which would suggest that the field gradient force could be responsible for the small additional shift as in aerated solution.…”
Section: J4mentioning
confidence: 99%
“…Waskaas and Kharkats [2][3][4] reported anodic shifts for iron in a variety of different electrolytes. The largest shift in 0.8 T was 45 mV in 1 M FeCl 3 . No such effect appeared for diamagnetic electrolytes such as MgCl 2 or ZnCl 2 , or for nonferromagnetic electrodes such as copper and zinc.…”
mentioning
confidence: 99%
“…3. According to Waskaas and Kharkats, 15) additional limiting current due to the magnetic field can be written as At weak magnetic fields:…”
Section: Potentiodynamic Testmentioning
confidence: 99%